Information System for Supporting Surveillance and Warning of Natural Disasters, Uttaradit Province - Kamching, Ratchada; Homhuan, Sakda (Area Based Development Research Journal, 2020)
This research paper aims to develop an information system to support surveillance and warning on natural disasters in Uttaradit province. The research process has designed collaboration among the academic department, the Office of Disaster Prevention and Mitigation, Uttaradit and UTT TEAM. The Information system designed for natural surveillance and warning can monitor and provide warnings of 3 natural hazards, which are 1) flood, 2) landslide, and 3) forest fire. The system is operated by analyzing the risk of natural disaster from data obtained from central geographic information system database with a collection of topographical data, climate data, and the past 10-year records provided by relevant agencies. Analysis is also based on real-time data received automatically from 3 devices that have been developed, which are 1) the environment detector 2) the water flow meter in the sub-basin and 3) the surveying and alarming equipment on landslide. The information system can analyze and assess the initial stage of disaster situation for the province. It processes the information to alert in specific conditions: 1) Warning of floods from the amount of water levels in the sub-basin every 5 minutes, 2) Landslide warning from the slope level data every week, 3) Forest fire alarm according to the hotspot data reported every 3 hours. In summary, corresponding data processing enables the Office of Disaster Prevention and Mitigation, Uttaradit and UTT TEAM to monitor the current situation and immediately plan to prevent natural disasters promptly and efficiently.